A Home of One's Own The Philosophy in Roger Scruton's Literary Writings. (16th July 2019) - Gescinska, Alicja
Abstract: Apart from being a prolific philosopher, Roger Scruton is also an accomplished writer of novels, poems, short stories, libretti and literary memoirs. In this article I will explore how Scruton's literary writings relate to his philosophy. I shall argue that one concept, pivotal to Scruton's philosophy, is also a main Leitmotiv of his literary work: home. The longing to be at home in the world is integral to our human nature. Several phenomena, as Scruton shows in his philosophy and literary works, are indispensable in order for us to be able to fulfil the desire to belong: beauty, oikophilia, and the ability to engage with each other as persons.